Clinical outcomes of modified intradermal vs. traditional intermittent suture technique in total knee arthroplasty: a single-center retrospective study - Huang, Changzhi; Xu, Nanyi; Zhang, Shimin; Lin, Jiuzao; Wang, Xiaoyong (Frontiers in Surgery, 2025)
BackgroundIn recent years, intradermal suture has gained increasing popularity due to its aesthetic incision and minimize scar formation. However, its efficacy compared to conventional intermittent suture in total knee arthroplasty (TKA) remains unclear. Therefore, we performed a retrospective study to evaluate the association between these two skin closure techniques and outcomes in patients underwent TKA.MethodsA total of 100 patients with unilateral knee osteoarthritis, who underwent TKA between October 2020 and October 2022 in our hospital, were selected based on inclusion and exclusion criteria. Patients were allocated to either a traditional suture group or a modified suture group according to skin closure method, with 50 patients in each group. The cohort consisted of 44 males and 56 females, with a mean age of 67.50 ± 6.14 years (range 57–79) and a mean disease duration of 8.26 ± 4.05 years (range 1–19). Hollander Wound Evaluation Score (HWES), Patient Scar Assessment Score (PSAS), and Observer Scar Assessment Score (OSAS) were compared 1,2,6,12,24 weeks postoperative, while the Range of Motion (ROM) were assessed 6,12,24 weeks post-surgery and Visual Analog Scale (VAS) were compared 1,3,5,7,14 days postoperative. Data collection was performed by independent assessors.ResultsCompared to the traditional group, the incision suture time, number of suture reactions, postoperative hospitalization time, PSAS, and OSAS of the modified group were lower. The VAS scores of the modified group were lower than those of the traditional group at 3, 5, and 7 days postoperative; the HWES scores at 1, 2, 6, 12, and 24 weeks postoperative; and the satisfaction scores of the incision aesthetics were significantly greater than those of the traditional group (P < 0.05). The number of incision dressing changes, incision alignment cases, incision exudation cases, and non-grade A healing cases in the modified group were slightly lower than those in the traditional group, with no statistical significance (P > 0.05). The flexion angle, extension angle, and flexion-extension angle of the knee joints in the two groups at 6, 12, and 24 weeks postoperative were significantly greater than those at baseline (P < 0.05), but the differences were not statistically significant (P > 0.05).ConclusionThe modified intradermal suturing technique was associated with significant improvements in scar condition and patient satisfaction with the aesthetic outcome of the incision. It was associated with shorter suturing time, lower incidence of suture reactions, and shorter postoperative hospitalization time compared with the traditional intermittent method.